(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to determine the effect of supervision of school principals on the quality of learning in Cluster 23 Lambheu, Darul Imarah District, Aceh Besar. The research used used a quantitative approach. Data collection techniques used in this research consist of interviews, questionnaires (questionnaires), observations (observations). The data analysis technique uses multiple linear regression analysis conducted using the help of the SPSS program version 20. The results of the study proved that the academic supervision of the principal had a significant influence on the quality of teacher learning in Cluster 23 Lambheu Darul Imarah Aceh Besar by 24.5%. Teacher performance has a significant influence on the quality of teacher learning services in Cluster 23 Lambheu Darul Imarah Aceh Besar by 20.4%. The academic supervision of the principal and teacher performance together have a significant influence on the quality of teacher learning by 39.9%.